THE STUDENTS’ QUESTION STRATEGY AND THEIR HIGHER ORDER THINKING SKILL IN LEARNING ENGLISH - Taufik, Muhammad; Nappu, Syamsiarna; Andi Baso, Farisha (English Language Teaching Methodology, 2024)
The objective of this research is to find out the Students' Question Strategies and their Higher Order Thinking Skills in Learning English.The method of this research is descriptive qualitative research. This research used two instruments; questionnaires and interviews. The subjects of this research were 10 students from grade IX namely 5 students from grade IX.4 and IX.5 of SMP Negeri 2 Sungguminasa. This research uses purposive sampling technique. The sample of this study consisted of 10 students with a population of 47 students from each class IX.4 and IX.5.The result of this research shows that learning oriented to higher order thinking skills or HOTS, can influence original thinking and according to the perspective of students to solve a problem in classroom especially in learning English. Therefore, the best way to see students' higher order thinking skills is to investigate a question strategy consisting of four; inferential questions, interpretation questions, transfer questions and hypothetic questions. Based on the result, student believe that by asking questions they will be able to explore English cognitively, and this can influence their higher order thinking skills.